2017
DOI: 10.7860/jcdr/2017/25529.9710
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax Induced Acute Respiratory Distress Syndrome – A Diagnostic and Therapeutic Dilemma in Preeclampsia

Abstract: A 27-year-old woman, G2P1L1 at 36 weeks gestation presented to our hospital with complaints of fever with chills and rigor since five days. There was no prior history of any obstetric or medical problems. She underwent lower segment caesarean section four years back for breech presentation.On examination, she was conscious and oriented, having mild pallor and icterus. Her temperature was 102.6°F, PR 128 bpm, RR 18/ min, BP 146/94 mmHg, O 2 saturation 100% at room air. Chest was clear with normal vesicular brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Acute respiratory distress syndrome is diagnosed in malaria infected pregnant women at lower rates compared to SMA, CM, and ARF, with overall proportion of ~0-4% in states including Rajasthan, Gujarat, and Andhra Pradesh (Table 3). ARDS can pose a veritable diagnostic and therapeutic dilemma as previously reported in a Pv-infected preeclamptic pregnant woman (78). Kochar et al (81) reported that pulmonary edema occurred in 13.3% of malaria infected pregnant women just after delivery in Rajasthan.…”
Section: Acute Respiratory Distress Syndrome/pulmonary Edemamentioning
confidence: 83%
See 2 more Smart Citations
“…Acute respiratory distress syndrome is diagnosed in malaria infected pregnant women at lower rates compared to SMA, CM, and ARF, with overall proportion of ~0-4% in states including Rajasthan, Gujarat, and Andhra Pradesh (Table 3). ARDS can pose a veritable diagnostic and therapeutic dilemma as previously reported in a Pv-infected preeclamptic pregnant woman (78). Kochar et al (81) reported that pulmonary edema occurred in 13.3% of malaria infected pregnant women just after delivery in Rajasthan.…”
Section: Acute Respiratory Distress Syndrome/pulmonary Edemamentioning
confidence: 83%
“…Using systematic review and meta-analysis approach, we recently showed that the overall prevalence of SM in individuals with Pv mono-infection was 29.3% in India, with lowest and highest rates in Karnataka (15.3%) and Uttarakhand (57.8%), respectively ( 5 ). In pregnant women, data on SM prevalence are greatly missing in India, and the studies on clinical patterns of severe MiP are focused and/or have evaluated few particular presentations only (e.g., ARDS, CM) ( 77 , 78 ). One study from Karnataka reported that 32.4% of malaria-infected patients were diagnosed with SM, and Pv was the main contributor of SM cases (56.6%) ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vivax malaria impacts the health of individuals of all ages causing repeated febrile episodes and severe anemia (15,17), clinical severity including hemolytic coagulation disorders, jaundice, coma, acute renal failure, rhabdomyolysis, porphyria, splenic rupture (4,18), and Acute Respiratory Distress Syndrome (ARDS) (19)(20)(21)(22). Fatal P. vivax cases are reported from all endemic regions across the globe (3,15,23).…”
Section: Introductionmentioning
confidence: 99%
“…Complete removal of the parasite from the human reservoir is therefore challenging (4,13), underscoring the need for innovative therapeutic strategies including the development of an effective vaccine (14,15). P. vivax malaria impacts the health of individuals of all ages causing repeated febrile episodes and severe anemia (14,16), clinical severity including hemolytic coagulation disorders, jaundice, coma, acute renal failure, rhabdomyolysis, porphyria, splenic rupture (3,17), and acute respiratory distress syndrome (18,19,20,21). Fatal P. vivax cases are reported from all endemic regions across the globe (1,14,22).…”
Section: Introductionmentioning
confidence: 99%